ENHANCING INNOVATION THROUGH HUMAN-AI COLLABORATION IN INDUSTRY 5.0: THE MEDIATING ROLE OF TRUST - Salleh, Shazwani Mohd; Rozali, Norhasyikin; Mat Khairi, Siti Murni; Che Sobry, Suheil; Rosli, Mohamad Shahrin (INTERNATIONAL JOURNAL OF INNOVATION AND INDUSTRIAL REVOLUTION (IJIREV), 2026)
Industry 5.0 envisions a human-centric industrial future where collaboration between humans and artificial intelligence (AI) enables sustainable innovation. However, despite the transformative potential of Human-AI Collaboration (HAIC), its impact on innovation remains inconsistent. This variability stems largely from insufficient attention to the psychological and relational mechanisms that facilitate effective partnership, particularly trust. The present research addresses this gap by proposing a conceptual framework that positions trust as the critical mediator between HAIC and innovation performance. Using a structured integrative review approach, we analyzed 28 peer-reviewed articles from the Scopus database (2020–2025) through thematic analysis to synthesize current knowledge and identify theoretical linkages. Our findings reveal that trust is not a static outcome but a dynamic, context-dependent construct shaped by transparency, explainability, reliability, and ethical AI design. Trust enables human operators to engage in risk-taking, knowledge sharing, and co-creative behaviors that directly enhance innovation in products, processes, and business models. This work provides a dual contribution: it unifies socio-technical systems theory with Industry 5.0 principles into a coherent mediation framework and offers actionable insights for designing “trustworthy-by-design” AI systems. The proposed framework underscores that technological sophistication alone is insufficient; fostering calibrated trust is essential to unlock the full innovative potential of human–AI symbiosis in next-generation manufacturing.